Bravest Warriors Most Ethereal, Most Human: Demon Soldiers in Chinese History - Wyatt, Don J. (Journal of religion and violence, 2020)
Often depicted as pitted in cosmic struggle against nobler multitudes of spiritual or heavenly warriors, when viewed from our modernist perspective, the ghostly or demon warriors of Chinese tradition are stigmatized as being, at best, ambiguous in status and, at worst, as perverse beings of consummately evil ill repute. However, discoveries from investigation into the historical origins of these demonic soldiers or troopers demand that we regard them as much more enigmatic in their roles and functions than is initially suggested. Documented earliest references indicate not only how the concept of demon warrior first arose for the purposes of furthering and facilitating the immortality ethos of religious Daoism. Also evident from these first written mentions is the clear and unassailable fact that the prototypes for these ghostly beings were unmistakably and very often unremarkably human. Subsequent literature, especially that surviving in the genre of early medieval tales of the strange, only reinforces the notion of these sometimes real and other times fantastical purveyors of violence as occupants of the permeable vortex thinly separating the human and the supernatural worlds, allowing them to manifest themselves at will and freely in either venue. Furthermore, we learn foremost how their primal function was not unlike that of Western guardian angels in being principally tutelary, with the tacit expectation that they should serve dutifully in defense of those who either cultivated or conjured them forth, ensuring the wellbeing of the living by acting as a kind of collective bulwark against the forces of death.